Evaluation of the Redesigned Enterotube—a System for the Identification of Enterobacteriaceae - Tomfohrde, K. M. (1973)
The redesigned Enterotube has been evaluated with 414 unknown Enterobacteriaceae cultures from the stock culture collection of the Center for Disease Control. When the Enterotube was used as recommended by the manufacturer, an average of 96.4% of these cultures were correctly identified. Only two groups (Salmonella and Edwardsiella) were identified with less than 90% accuracy (89.2 and 87.5%, respectively). The Enterotube now provides a convenient, rapid, and accurate test system for the identification of typically reacting enteric bacteria.